1998
DOI: 10.1149/1.1838889
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Recombination Properties of Copper‐Silicide Precipitates in Silicon

Abstract: Copper-silicide precipitates in silicon obtained after copper diffusion and quench in different liquids were studied by transmission electron microscopy and capacitance spectroscopy techniques. A correlation between the quenching rate, geometric size, and deep level spectra of the copper-silicide precipitates was established. The unusually wide deep level spectra are shown to be due to a defect-related band in the bandgap. The parameters of the band are evaluated using numerical simulations. A positive charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 11 publications
7
68
0
Order By: Relevance
“…Such extended defects introduce a continuous band of energy states in the upper half of the bandgap, from E c À 0:15 eV to E c À ð0:4…0:5Þ eV 37,38 with an estimated electron capture cross-section r n ¼ 3 Â 10 À16 cm 2 . 39 Macdonald et al showed through LS methods that the impact of this distributed energy band can be approximated via two non-interacting SRH defects with energy levels located at E c À 0:15 eV and E c À 0:58 eV, which approximately correspond to the extremes of the aforementioned energy band.…”
Section: Comparison With Literature Data and Discussionmentioning
confidence: 99%
“…Such extended defects introduce a continuous band of energy states in the upper half of the bandgap, from E c À 0:15 eV to E c À ð0:4…0:5Þ eV 37,38 with an estimated electron capture cross-section r n ¼ 3 Â 10 À16 cm 2 . 39 Macdonald et al showed through LS methods that the impact of this distributed energy band can be approximated via two non-interacting SRH defects with energy levels located at E c À 0:15 eV and E c À 0:58 eV, which approximately correspond to the extremes of the aforementioned energy band.…”
Section: Comparison With Literature Data and Discussionmentioning
confidence: 99%
“…It has been observed recently by transmission electron microscopy that the gettering of Cu in n-type Si is accompanied by the formation of copper-silicide precipitates [10]. The enhanced Cu precipitation in n-type Si was explained by the formation of precipitates that are negatively charged or neutral in n-Si, hence attracting interstitial Cu i + , but positively charged in p-Si [19,10]. We would like to point out that acceptor-like substitutional Cu S n− should form efficient nucleation centers for the precipitation of Cu i + atoms.…”
mentioning
confidence: 99%
“…In mc-Si, copper can precipitate homogeneously in the silicon lattice or heterogeneously at grain boundaries, stacking faults, and dislocations. 35 Homogeneous precipitation requires a quasi-Fermi level above E c -0.2 eV, 36 which is not achieved at these copper levels 15 during slow air cooling 21 after oxidation or Cu in-diffusion. Therefore, copper is expected to precipitate heterogeneously at extended defects in mc-Si.…”
Section: Discussionmentioning
confidence: 99%